Trends of in-hospital maternal mortality during the COVID-19 pandemic in southern Morocco – analysis of a time series from 2016–2022 - Oumbarek, Keltouma; Razine, Rachid; Lkoul, Abdelmajid; Mahlaq, Safiya; El Hilali, Samia; Lahlou, Laila; Baba, Mohamed Amine; Kharbach, Ahmed; Obtel, Majdouline (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. The aim of this study was to compare trends of in-hospital maternal mortality in southern Morocco be fore and after the COVID-19 pandemic emerged in the Kingdom in March 2020. Material and methods. We conducted a retrospective study of a time series of hospital maternal deaths from January 2016 to December 2022. Data were collected from maternal death registers and monthly reports from maternity departments of six public hospitals in Souss Massa region (one regional and five provincial hospitals). Results. 216 maternal deaths occurred during the study period, 112 before and 104 during the pandemic. The highest annual maternal mortality ratio (MMR) was observed in 2021 (207.41 deaths/100,000 live births). Trends of monthly MMR showed a significant increase during the pandemic compared with the pre-pandemic period (p=0.002). Furthermore, an extremely high MMR value (977.57/100,000 live births) was noted in August 2021 (the Delta wave). There was a significant difference in the distribution of causes of maternal death. Proportion of indirect causes were tripled during the pandemic (from 8% to 24%), with 17/104 (16.3%) deaths related to SARS-CoV-2 pneumonia. Conclusion. In-hospital MMR increased in public hospitals of the Souss Massa region during the COVID-19 pandemic, particu larly in the third quarter of 2021.
The ethical approval was granted by the Ethics Committee for Biomedical Research of the Faculty of Medicine and Pharmacy Mohammed V in Rabat, Morocco (Reference: CERB G/23).
Keywords: COVID-19 pandemic; maternal mortality; southern Morocco; time series